PENGARUH KECERDASAN EMOSIONAL TERHADAP KINERJA MELALUI KOMPETENSI DAN MOTIVASI DOSEN KEPERAWATAN DI KOTA MAKASSAR - La Ode As Ari; Hasmin Tamsah; Eddyman Eddyman (Pascasarjana STIE Amkop Makassar, 2019)
ABSTRACKThis research was conducted on November 3, 2018 until December 3, 2018. The type of research used was quantitative with an associative type, because researchers wanted to know whether there were any influences between the variables through testing the formulated hypothesis, the population in this study amounted to 60 respondents and determining the sample based on total sampling, the tools used in data collection are questionnaire.The results of this study indicate that based on the value of tcount of 0.023 it is smaller than t table 0.256, which means that the mediation parameters have a positive and insignificant effect. This means that emotional intelligence has a positive and not significant effect indirectly on lecturer performance through the competence of nursing lecturers in the city of Makassar. Then the Sixth Hypothesis (H6) is rejected, while the value of t count of 0.363 is greater than ttable 0.256, which means that the parameter the mediation had a positive and significant effect. This means that emotional intelligence has a positive and significant effect indirectly on lecturer performance through the motivation of nursing lecturers in the city of Makassar, so the Sixth Hypothesis (H6) is accepted.Keywords: Emotional Intelligence, Competence, Motivation, Performance